2004
DOI: 10.1111/j.1364-3703.2004.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Homologous soybean and Arabidopsis genes share responsiveness to cyst nematode infection

Abstract: SUMMARY We previously isolated a partial soybean cDNA clone (D17.1) whose corresponding transcript increases in susceptible roots 1 day post inoculation (dpi) with the soybean cyst nematode, Heterodera glycines. Here we isolated the corresponding full-length cDNA from a soybean cDNA library and designated this gene of unknown function Gm17.1. Time course RNA gel blot analyses revealed that Gm17.1 mRNA steady-state levels were elevated in soybean roots following H. glycines infection up to at least 6 dpi. For f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 95 publications
1
9
0
Order By: Relevance
“…The presence of the parasite induces drastic changes in plant gene expression (reviewed by Gheysen and Fenoll, 2002). Several molecular approaches have been exploited to pinpoint changes in plant gene expression as a result of nematode infections, including protein analysis (Rahimi et al, 1993), promoter reporter-gene fusions (Barthels et al, 1997;Favery et al, 1998Favery et al, , 2004Goddijn et al, 1993;Goverse et al, 1998;Mazarei et al, 2003Mazarei et al, , 2004Niebel et al, 1996;Puzio et al, 2000), in situ hybridization (Goellner et al, 2001;Niebel et al, 1993), reverse transcriptase-polymerase chain reaction (RT-PCR) (Karczmarek et al, 2008;Vaghchhipawala et al, 2001), differential display (Hermsmeier et al, 1998(Hermsmeier et al, , 2000Vercauteren et al, 2001), microarray analysis (Alkharouf et al, 2006;Hammes et al, 2005;Ithal et al, 2007;Jammes et al, 2005;Khan et al, 2004;Puthoff et al, 2003Puthoff et al, , 2007 and serial analysis of gene expression (SAGE) (Uehara et al, 2007). The outcome of these studies has culminated in the identification of a relatively small group of genes that are involved in a wide range of nematode-affected plant processes.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the parasite induces drastic changes in plant gene expression (reviewed by Gheysen and Fenoll, 2002). Several molecular approaches have been exploited to pinpoint changes in plant gene expression as a result of nematode infections, including protein analysis (Rahimi et al, 1993), promoter reporter-gene fusions (Barthels et al, 1997;Favery et al, 1998Favery et al, , 2004Goddijn et al, 1993;Goverse et al, 1998;Mazarei et al, 2003Mazarei et al, , 2004Niebel et al, 1996;Puzio et al, 2000), in situ hybridization (Goellner et al, 2001;Niebel et al, 1993), reverse transcriptase-polymerase chain reaction (RT-PCR) (Karczmarek et al, 2008;Vaghchhipawala et al, 2001), differential display (Hermsmeier et al, 1998(Hermsmeier et al, , 2000Vercauteren et al, 2001), microarray analysis (Alkharouf et al, 2006;Hammes et al, 2005;Ithal et al, 2007;Jammes et al, 2005;Khan et al, 2004;Puthoff et al, 2003Puthoff et al, , 2007 and serial analysis of gene expression (SAGE) (Uehara et al, 2007). The outcome of these studies has culminated in the identification of a relatively small group of genes that are involved in a wide range of nematode-affected plant processes.…”
Section: Introductionmentioning
confidence: 99%
“…Many crops and Arabidopsis share similar modes of action regarding disease resistance. For example, the homologues of the avr genes of bean and pea (Dangl et al, 1992) and an SCNinduced gene of soybean (Mazarei et al, 2004) were identified in Arabidopsis and behaved in a similar fashion. Conversely, Arabidopsis resistance genes effective against crop pathogens have been identified and found to have the same functionality in crops.…”
Section: Figmentioning
confidence: 96%
“…Mazarei et al . (), who analysed the expression of the Arabidopsis homologue of a soybean gene that was up‐regulated during SCN infection, found that the pair of homologues behaved in a similar fashion following cyst nematode infection, and that the promoter of the Arabidopsis homologue functioned normally in soybean. They suggested that Arabidopsis shares molecular events of cyst nematode parasitism with soybean, and that the Arabidopsis– H. schachtii interaction is a suitable model for the soybean– H. glycines pathosystem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence showed that phytohormones play an important role in response to cyst nematode infection and syncytium formation. GUS activity has been detected in syncytia when fused with auxin-responsive plant promoters (Karczmarek et al 2004, Mazarei et al 2004. Using auxin-insensitive tomato and Arabidopsis mutants, Goverse et al (2000) demonstrated the direct involvement of auxin in feeding site formation.…”
Section: Chapter 1 General Introductionmentioning
confidence: 99%